Positions on Regulations Affecting Auditing and Nonauditing Activities - López Gavira, Rosario (2014)
The change in regulations that occurred in Spain in the domain of auditing has led to the analysis of regulations according to the positions adopted by different groups involved in the auditing market. The purpose of this study was to investigate the positions taken by professionals involved in this sector regarding those aspects of the law that regulate the provision of services other than the auditing of annual accounts, with a view to obtaining relevant conclusions for the regulation of the auditing activity. Findings show the existence of three professional subgroups according to the level of global prohibition of the incompatibilities analyzed and the level of importance assigned to the prohibitions in two important groups of prohibitions. The difference between these professional groups is analyzed in terms of their level of prohibition in comparison with the law. Other results show the most important variables for measuring a firm’s degree of independence.